Observation of long-lived phosphorescence in Au(i) complexes bearing chromophoric (N-heterocyclic carbene) ligands. Issue 5 (8th February 2023) - Van Orman, Evan P.; Wolf, Steven M.; Yung, Zheng; Holt, Ethan D.; de La Harpe, Kimberly; Zeller, Matthias; Grusenmeyer, Tod A.; Gray, Thomas G.
Abstract : Long-lived phosphorescence has been observed at room temperature in two gold(i ) complexes of a fluorenyl-substituted N-heterocyclic carbene. Abstract : Synthesis and optical characterization of two new gold(i ) complexes bearing chromophoric N-heterocyclic carbene (NHC) ligands are described. Ligands with electron-releasing (diphenylamino) and electron-withdrawing (benzothiazolyl) substituents are described, and metalation with gold(i ) bromide is demonstrated. Crystallographic characterization reveals both complexes to have linear, two-coordinate gold and an absence of aurophilic interactions in the solid state. The absorption spectra of both gold(i ) complexes are similar to the free ligand absorption spectra indicating ligand localized π–π* absorption. The new gold complexes show moderate fluorescence and observable phosphorescence; binding of a single gold atom suffices to populate triplet excited states. The fluorescence of the benzothiazolyl derivative is π–π* in nature, while the fluorescence of the diphenylamino derivative is charge-transfer in nature. The phosphorescence of both complexes is vibronically structured, indicative of metal-perturbed π–π* character. Phosphorescence at 298 K persists for hundreds of microseconds. Intersystem crossing is the dominant excited state kinetic pathway with quantum yields of intersystem crossing greater than 50% for both gold complexes. Density-functional theory calculations indicate that the lowest excited singlet and triplet states are dominated by the carbene-fluorenyl-substituent conjugate. We believe the incorporation of gold as a heavy atom through a strongly σ-donating and moderately π-accepting NHC-linker provides a general strategy for achieving NHC complexes with phosphorescence.